Experimental Models of Gulf War Illness, a Chronic Neuropsychiatric Disorder in Veterans. Issue 3 (22nd March 2023) - Reddy, Doodipala Samba; Wu, Xin; Singh, Tanveer; Neff, Michael
Abstract: Gulf War illness (GWI) is a chronic multifaceted condition with debilitating pain and fatigue, as well as sleep, behavioral, and cognitive impairments in war veterans. Currently, there is no effective treatment or cure for GWI; therefore, there is a critical need to develop experimental models to help better understand its mechanisms and interventions related to GWI‐associated neuropsychiatric disorders. Chemical neurotoxicity appears to be one cause of GWI, and its symptoms manifest as disruptions in neuronal function. However, the mechanisms underlying such incapacitating neurologic and psychiatric symptoms are poorly understood. The etiology of GWI is complex, and many factors including chemical exposure, psychological trauma, and environmental stressors have been associated with its development. Attempts have been made to create GWI‐like symptomatic models, including through chronic induction in mice and rats. Here, we present a brief protocol of GWI in rats and mice, which exhibit robust neuropsychiatric signs and neuropathologic changes reminiscent of GWI. This article provides a guide to working protocols, application of therapeutic drugs, outcomes, troubleshooting, and data analysis. Our broad profiling of GWI‐like symptoms in rodents reveals features of progressive morphologic and long‐lasting neuropsychiatric features. Together, the GWI model in rodents shows striking consistency in recapitulating major hallmark features of GWI in veterans. These models help identify mechanisms and interventions for GWI. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Experimental induction of Gulf War illness in rats Support Protocol 1 : Monitoring of Gulf War illness signs and neuroimaging analysis in rats Basic Protocol 2 : Experimental induction of Gulf War illness in mice Support Protocol 2 : Monitoring of Gulf War illness signs and neuropathology analysis in mice